2017
DOI: 10.1039/c7ra03334f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the water repellency of wood surfaces by atmospheric pressure cold plasma deposition of fluorocarbon film

Abstract: This study explores the fluorocarbon deposition on wood by atmospheric pressure plasma, with the focus on higher water repellency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The hydrophobization of wood surfaces through plasma treatments with fluoroalkanes and organosilicons also received some attention over the last five years. Notably, de Cademartori et al created a fluorocarbon film on white spruce and Brazilian cedar by polymerizing octofluoropropane with a DBD plasma [198]. They found that longer treatment periods would lead to higher hydrophobicity, with optimal water contact angles of 135.2 • and 129.8 • on the spruce and cedar, respectively.…”
Section: Plasma Modificationmentioning
confidence: 99%
“…The hydrophobization of wood surfaces through plasma treatments with fluoroalkanes and organosilicons also received some attention over the last five years. Notably, de Cademartori et al created a fluorocarbon film on white spruce and Brazilian cedar by polymerizing octofluoropropane with a DBD plasma [198]. They found that longer treatment periods would lead to higher hydrophobicity, with optimal water contact angles of 135.2 • and 129.8 • on the spruce and cedar, respectively.…”
Section: Plasma Modificationmentioning
confidence: 99%
“…A wide spectrum of organic, photocatalytic, and silver ion antimicrobial agents have been applied to date as coatings [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. This includes silver nanoparticles [52], combinations of various metal ions and various metalic nanoparticles [53,54], and combinations of all of the above [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Photocatalytic agents (e.g., titanium dioxide, ZnO) require conditions of water and oxygen and UV A wide spectrum of organic, photocatalytic, and silver ion antimicrobial agents have been applied to date as coatings [33][34][35][36][37][38][39][40][41][42]…”
Section: Increased Durabilitymentioning
confidence: 99%
“…Photo-degradation occurs due to the extensive cleavage of wood cell components. Cleavage of the phenolic sides of lignin by absorbance of ultraviolet (UV) light is more rapid than the other wood polymers (e.g., cellulose and hemicelluloses) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The degradation of a wood surface proceeds by removal of photo-degraded wood fragments with rain and exposure of the subjacent layers to further erosion [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One path to improve the surface properties of wood is through modification techniques. Among various emerging surface modification techniques, plasma treatment has been extensively used during the recent decade [ 4 , 14 , 15 , 16 ]. It is a dry and clean process with minor environmental concerns.…”
Section: Introductionmentioning
confidence: 99%